Social Impact Investment International Perspectives and Suggestions for Vietnam - Nguyen, Thuy Linh (H. : ĐHQGHN, 2017)
This paper presents an exploratory analysis of impact investing from the state of play of this phenomenon in the international context generally, and in Australia particularly. It then provides an overview of the current status of impact investing in Vietnam business context. A discussion of what international experiences could be adopted in the circumstance of Vietnam is presented.